An interactive web-based programme on relapse management for people with multiple sclerosis (POWER@MS2) - development, feasibility, and pilot testing of a complex intervention - Wenzel, Lisa; Heesen, Christoph; Peper, Julia; Grentzenberg, Kristina; Faßhauer, Edeltraud; Scheiderbauer, Jutta; Thale, Frithjof; Meyer, Björn; Köpke, Sascha; Rahn, Anne Christin (Frontiers in Neurology, 2022)
Introduction Despite the lack of high-quality evidence regarding its long-term effectiveness, intravenous corticosteroid therapy is recommended as the standard treatment of acute multiple sclerosis relapses in Germany. High financial expenses and the equivalent effectiveness of oral corticosteroid therapy contrast with this trend. There is an urgent need to provide patients with evidence-based and comprehensible information on relapse management and to actively involve patients in relapse treatment decisions. Web-based decision support on relapse management could be an effective measure to empower people with multiple sclerosis making informed treatment decisions. Objectives To develop a web-based programme on relapse management for people with multiple sclerosis and evaluate the feasibility and acceptability of the intervention. Methods The study followed the first two phases of the UK Medical Research Council Framework for complex interventions. The first phase involved the development of an interactive web-based programme on relapse management. The second phase focused on the feasibility and pilot testing of the programme with people with multiple sclerosis and experts with a professional background in multiple sclerosis. Data was obtained using questionnaires with closed- and open-ended questions as well as qualitative semi-structured telephone interviews. Quantitative data was analyzed descriptively, whereas qualitative data was clustered by topic. Results Feasibility of the intervention programme was tested with 10 people with multiple sclerosis and 10 experts. Feasibility testing indicated good practicability and acceptance of the content. After revision, the programme was piloted with seven people with multiple sclerosis and three experts. The results showed good acceptance in both groups. Based on the feedback, a final revision was performed. Conclusion Feasibility and pilot testing indicated good user-friendliness, acceptance, and practicability of the programme. The programme is currently evaluated in a randomized controlled trial (Registration Number on ClinicalTrials.gov: NCT04233970). It is expected that the programme will have a positive impact on patients' relapse management and strengthen their autonomy and participation.